Discovering real business requirements for software project success - Goldsmith, Robin F. (Artech House, 2004)
Annotation While a number of books on the market deal with software requirements, this is the first resource to offer you a methodology for discovering and testing the real business requirements that software products must meet in order to provide value. The book provides you with practical techniques that help prevent the main causes of requirements creep, which in turn enhances software development success and satisfaction among the organizations that apply these approaches. Complementing discovery methods, you also learn more than 21 ways to test business requirements from the perspectives of assessing suitability of form, identifying overlooked requirements, and evaluating substance and content. The powerful techniques and methods presented are applied to a real business case from a company recognized for world-class excellence. You are introduced to the innovative Problem Pyramidtm technique which helps you more reliably identify the real problem and requirements content. From an examination of key methods for gathering and understanding information about requirements, to seven guidelines for documenting and communicating requirements, while avoiding analysis paralysis, this book is a comprehensive, single source for uncovering the real business requirements for your software development projects.